Earth System Model Evaluation Tool (ESMValTool) v2.0 - An extended set of large-scale diagnostics for quasi-operational and comprehensive evaluation of Earth system models in CMIP - Eyring, Veronika (2020)
824084 grant no. 274762653 grant no. CMIP6-DICAD